The Mathematical Literacy of Vocational Students in Discovery Learning Using E-Worksheet - Maya Kusuma, Sarli Bamoris; Budi Waluya, Stevanus; Masrukan, Masrukan (Universitas Negeri Semarang, 2021)
The aim of this study was to find out the level of mathematics literacy skills of vocational students in discovery learning using e-worksheets. The research method used is a mix method with a research focus on the mathematical literacy skills of vocational high school students specifically in spatial abilities of geometric transformation material in discovery learning with e-worksheet assisted product assessment. The subjects of this study were students of XI class of Automation and Office Management of SMK Negeri 1 Demak. The qualitative data analysis was carried out by analyzing mathematical literacy skills in terms of students' spatial abilities. The quantitative data were tested by using the One Sample t-test, Paired Sample t-test, and Independent Sample t-test. The results showed that e-worksheet using discovery learning was able to develop students 'mathematical literacy abilities, gave positive responses to students. This study also found that students' spatial abilities would be relevant to their level of mathematical literacy skills.